Effect of abiotic stress under light and dark conditions on carotenoid content in pumpkin (Cucurbita moshata) calluses - Shahidan, Norshazila; Othman, Rashidi; Jaswir, Irwandi; Hashim, Yumi Zuhanis Has-Yun (Journal of Fundamental and Applied Sciences, 2017)
The aim of this study was to observe the effect of abiotic stress under light and dark conditions on pumpkin calluses carotenoid. Plant elicitors used to create abiotic stress in this study were Polyethylene Glycol 4000 for drought stress, Jasmonic Acid and Salicylic Acid for hormones stress and Murashige and Skoog Salt for control and half strength nutrients. Carotneoid content was determined using High Performance Liquid Chromatography. Under light condition, the value of lutein was in range 0.554 + 0.107 µg/g to 0.169+ 0.003 µg/g and β-carotene was in range of not detected up to 8.133 + 0.088 µg/g. Differ to dark condition, a trace amount of lutein was detected in each treatments and the highest amount of β-carotene was detected in Polyethylene glycol treatment (5.313 + 0.051 µg/g). Carotenoid content varies in each treatment due to adaptation of pumpkin calluses with abiotic stress induced to them.